2020
DOI: 10.7717/peerj.8521
|View full text |Cite
|
Sign up to set email alerts
|

Association of the CACNA2D2 gene with schizophrenia in Chinese Han population

Abstract: Background Schizophrenia (SCZ) is a severely complex psychiatric disorder in which ~80% can be explained by genetic factors. Single nucleotide polymorphisms (SNPs) in calcium channel genes are potential genetic risk factors for a spectrum of psychiatric disorders including SCZ. This study evaluated the association between SNPs in the voltage-gated calcium channel auxiliary subunit alpha2delta 2 gene (CACNA2D2) and SCZ in the Han Chinese population of Northeast China. Methods A total of 761 SCZ patients and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“… 62 Meanwhile, another study showed that SORBS1 might be a new susceptibility gene for diabetic nephropathy. 63 CACNA2D2 is the voltage-gated calcium channel auxiliary subunit alpha2delta2 gene that encodes a calcium channel protein, 64 and Huang et al identified CACNA2D2 as a diabetes-related atherogenesis gene. 65 Besides, GREM2 and HSPB8 are closely related to inflammatory response, 66 , 67 suggesting a regulatory role in the T1DM macrophages inflammation.…”
Section: Discussionmentioning
confidence: 99%
“… 62 Meanwhile, another study showed that SORBS1 might be a new susceptibility gene for diabetic nephropathy. 63 CACNA2D2 is the voltage-gated calcium channel auxiliary subunit alpha2delta2 gene that encodes a calcium channel protein, 64 and Huang et al identified CACNA2D2 as a diabetes-related atherogenesis gene. 65 Besides, GREM2 and HSPB8 are closely related to inflammatory response, 66 , 67 suggesting a regulatory role in the T1DM macrophages inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 761 SCZ patients and 775 healthy controls without any personal or family history of mental illness were enrolled in this study. More details of the data collection are described in a previous paper ( Fu et al, 2020 ). All subjects were recruited after providing written informed consent.…”
Section: Methodsmentioning
confidence: 99%